Buddhisme dan Budaya Lokal - Sril Lestari (Jurnal Ilmiah Kampus: Sati Sampajanna, 2023)
Religion cannot be separated from the culture in which it develops. This study uses discourse analysis about Buddhism and local culture. The method used in this study is Discourse Analysis. Namely a study methodology that focuses on the use of texts used in social and cultural contexts to communicate meaning. In the study "Buddhism and Local Cultures," discourse analysis is used to understand how Buddhism's teachings and practices are discussed and translated in specific local cultures. The research results show that Buddhism has a long history of interacting and adapting to various local cultures throughout the world. In the process, Buddhism not only exerted influence on local culture, but was also influenced and enriched by it. Central Buddhist principles such as tolerance, openness, and respect for diversity, allow him to embrace and nurture local cultures, while maintaining the core of his teachings. However, Buddhism also seeks to critically assess aspects of local culture that may conflict with its basic teachings. Thus, in interacting with local culture, Buddhism practices a balanced approach between adaptation and maintaining core values. This reflects how Buddhism plays an active role in nurturing and nurturing local culture, while ensuring that its central principles are respected and maintained